The novelist's film [videorecording (Blu-ray)] - Lee, Hye-yeong; Kim, Min-hŭi, 1982-; Seo, Younghwa (Cinema Guild, 2023)
Junhee is a novelist who's grown disenchanted with her writing. On a trip to see an old friend, she runs into a film director who was set to adapt one of her novels before the project fell through. One chance encounter leads to another and soon she finds herself having lunch with Kilsoo, a well-known actress also questioning he role as an artist. It's then that Junhee has an epiphany: she will make a film starring Kilsoo. It won't be like other films. It will be the novelist's film.